ANALISIS KESIAPAN BELAJAR SISWA KELAS IV PADA PEMBELAJARAN BERDIFERENSIASI DI SDN BANYUMANIK 03 - Intan, Rizki Septy Nur; Ulia, Nuhyal (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research is motivated by the importance of student learning readiness in differentiated learning. The purpose of this research is to describe the learning readiness of fourth grade students of SDN Banyumanik o3 in differentiated learning. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews and questionnaires as data collection techniques. The results of this study indicate that student readiness is in the high category with an average percentage of 78.65%. Motor development is the indicator with the highest percentage (82.59%). Meanwhile, motivation is the indicator with the lowest percentage (75%). Efforts made by teachers in the process of meeting students' learning needs are by implementing differentiated learning to adjust learning methods and strategies according to student characteristics. This research confirms that student learning readiness is an aspect that needs to be considered to design learning strategies appropriately. Teachers need to continuously adapt learning to students' needs and readiness to ensure that all students can learn optimally. In addition, by understanding students' learning readiness, teachers can optimize the achievement of learning objectives and support students' potential development